Effect of obesity on bladder cancer and renal cell carcinoma incidence and survival. Issue 5 (September 2017) - Gild, Philipp; Ehdaie, Behfar; Kluth, Luis A.
Abstract : Purpose of review: The prevalence of obesity has risen dramatically in the general population and among cancer survivors in the last three decades. In this review, we highlight the impact of obesity on carcinogenesis and survival with a focus on bladder cancer and renal cell carcinoma (RCC). Recent findings: Obesity presents an established risk factor for an up to 1.8-fold relative risk of RCC. Data with regard to bladder cancer are less abundant but support this association as well. Possible biological mechanisms involved are the insulin/insulin-like growth factor pathway, sex steroids, adipokines and chronic inflammation as well as treatment disparities within normal weight versus obese patients. With regard to survival, no conclusion can be drawn in either tumor entity at this time because of contradictory findings. These can in part be attributed to methodological limitations, while at the same time data exist to support the notion that obese patients exhibit less aggressive tumors. Summary: Obesity drives cancer risk in RCC and potentially bladder cancer. Evidence regarding survival has been contradictory and therefore no clear-cut recommendation can be made regarding weight management in cancer survivors despite to maintain a healthy lifestyle. However, given the future cancer burden that obesity will constitute, physicians should encourage weight loss and help prevent weight gain in the general population.